Women, work, and the family in Europe - Drew, Eileen P.; Emerek, Ruth; Mahon, Evelyn (Routledge, 1998)
A new and timely analysis of major changes in society within the extended European Union. Addresses the consequences of altered family forms, the restructuring of the labour markets and the conflicting demands of family and working life.